Sistem Pendukung Keputusan Validasi Data Pegawai Polres Labuhanbatu dengan Metode AHP (Analytical Hierarchy Process) - Samsir, Samsir; Dalimunthe, Abdul Hakim; Aditya, Rahmad (Universitas Labuhanbatu, 2025)
Shipping device processing is based on inquiries and orders from the warehouse department. If the warehouse does not place orders, the sales process will not be completed so the warehouse is often empty and the revenue method is stuck. The process of ordering scientific gadgets requires approval from the stock department to place an order, so it takes a lot of time to review stock devices. PT. Murti Indah Sentosa is a clinical equipment distribution organization. With the DES method approach, this can overcome the problems faced by employers. because double exponential smoothing is used while there are seasonal factors of fashion and behavior within the inMenuation. The double exponential smoothing method can be used for most types of table-bound and table-unbound inMenuation, as long as the data does not include seasonality. The effect of this observation is that through the application of the double exponential smoothing technique, clinical tool forecast reports can be obtained and determined in a timely and environmentally friendly manner and applied within the organization to produce an inventory effect of scientific tools according to the dreams and needs of the company. agent. In the next season, garage spaces can be filled and goals can be scored.